Relevansi Pidana Mati Terhadap Tindak Pidana Narkotika Dalam Prespektif Pembaharuan Hukum Pidana - Abdul Halim Lubis; Ania Margaini (Sanskara Hukum dan HAM, 2022)
The death penalty in the Draft Criminal Law Code (RKUHP) is currently in effect. Therefore, this study aims to examine and understand how the death penalty law should be applied in Indonesian criminal penalties. The method used by the author in this research is a normative juridical method. The law of narcotics crime which has been regulated in draft criminal law code including the death penalty. The formulation of the death penalty in a national crime has become a conflict of thought among criminal experts in Indonesia. The concept of the Draft Criminal Code is based on a point of view by considering the idea of balance. It is also hoped that later with the death penalty, it is hoped that the death penalty will be able to restrict the illegal circulation and misappropriation of drugs through the formation of a national criminal law. The impact of this research can prove that the implementation of punishment for narcotics criminals must be carried out in order to prove humans on a large scale by murdering one person and giving the convict the death penalty.